Twenty-four-hour blood pressure profile in idiopathic REM sleep behavior disorder. Issue 2 (23rd September 2021) - Terzaghi, Michele; Pilati, Laura; Ghiotto, Natascia; Arnaldi, Dario; Versino, Maurizio; Rustioni, Valter; Rustioni, Gianluca; Sartori, Ivana; Manni, Raffaele
Abstract: Study Objectives: To determine whether autonomic dysfunction in idiopathic REM sleep behavior disorder (iRBD) affects circadian blood pressure (BP) profile. Methods: Twenty-one iRBD (mean age 68.8 ± 6.4, mean age at onset 62.2 ± 9.3), 21 drug-free de novo Parkinson's disease (PD) and 21 control participants (HCs), comparable for age and sex, underwent 24-h ambulatory BP monitoring. A prospective follow-up study was performed to evaluate the occurrence of neurodegenerative disorders in the iRBD cohort. Results: In the iRBD group, nighttime systolic BP (SBP) was higher (124.0 ± 20.0, p = .026), nocturnal BP decrease lower (4.0 ± 8.7% for SBP and 8.7 ± 8.0% for diastolic BP [DBP], p = .001), and nondipping status more frequent (71.4% for SBP and 52.4% for DBP; p = .001 and p = .01, respectively) than in the HCs. Reverse dipping of SBP was found in 23.8% ( p = .048) of the iRBD participants. Nondipping status was not associated with differences in gender, age, disease duration, age at disease onset, UPDRS score, presence of antihypertensive therapy, or polysomnographic measures. Patients with PD showed daytime and nighttime BP profiles comparable to those observed in iRBD. A subgroup analysis considering only the participants without antihypertensive therapy (12 iRBD, 12 PD) showed results superimposable on those of the whole iRBD and PD groups. Longitudinal follow-up (mean 5.1 ± 1.9 years) showed no differences in BP profile at baseline between converters ( n = 6) and nonconverters. Conclusions: Twenty-four-hour BP control was impaired in iRBD. This impairment, similar to patterns observed in de novo PD, consisted of reduced amplitude of nocturnal dipping and increased frequency of nondipping status. These findings could have implications for cardiovascular morbidity and mortality in iRBD.